Komunikasi Antarbudaya Mahasiswa Minang dalam Menghadapi Gegar Budaya di Bogor - Lowu, Alexandre Rachel; Suparman; Yafnida Julia Andriani; Salwa Putri Awalina; Khalila Zahra Maharani (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2025)
This research aims to analyze the forms of intercultural communication carried out by ethnic Minang students in facing culture shock in Bogor. Students who come from outside the region experience the phenomenon of culture shock which causes anxiety and tension. This is a result of the differences between the culture in the area of ​​origin and the place of origin. The research uses qualitative methods with data collection techniques through interviews. There were five informants consisting of ethnic Minang students who experienced culture shock when they moved to Bogor. Data analysis is based on Miles and Huberman's theory, namely data reduction, data presentation, and drawing conclusions. The research results show that Minang students have diverse forms of intercultural communication, including the use of verbal, non-verbal communication, and cultural adaptation strategies. Intercultural communication is implemented to deal with the phenomenon of culture shock.